Specialty‐Based Variations in Spinal Cord Stimulation Success Rates for Treatment of Chronic Pain. Issue 4 (2nd April 2017) - Hussaini, Syed Mohammed Qasim; Murphy, Kelly Ryan; Han, Jing L.; Elsamadicy, Aladine A.; Yang, Siyun; Premji, Alykhan; Parente, Beth; Xie, Jichun; Pagadala, Promila; Lad, Shivanand P.
Abstract : Objectives: Spinal cord stimulation (SCS) has emerged as an appropriate modality of treatment for intractable chronic pain. The present study examines variations in SCS trial‐to‐permanent conversion rates based on provider types performing the procedure. Materials and Methods: We designed a large, retrospective analysis using the Truven MarketScan data base analyzing adult SCS patients with provider information available, with or without IPG implantation from the years 2007–2012. Patients were categorized based on provider type performing the implantation including anesthesiologists, neurosurgeons, orthopedic surgeons, and physical medicine and rehabilitation (PM&R). Univariate and multivariate models identified factors associated with successful conversion. Results: A total of 7667 unique instances of SCS implants were identified across five providers. Overall, 4842 (63.2%) of those receiving trials underwent permanent SCS system implantation. Anesthesiology performed the majority of implants (62.8%), followed by neurosurgery (22.0%), orthopedic surgery (10.2%), and PM&R (5.3%). Compared to anesthesiologists, both neurosurgeons (OR 10.99, 95% CI [9.11, 13.25]; p  < 0.001) and orthopedic surgeons (OR 4.64, 95% CI [3.81, 5.65]; p  < 0.001) had significantly higher conversion rates, while PM&R (OR 0.71, 95% CI [0.58, 0.87]; p  = 0.001) had significantly lower. Percutaneous implants comprised 5473 (71.4%) of all implants. Neurosurgeons and orthopedic surgeons performed a significantly greater number of paddle implants among the different providers ( p  < 0.0001). Explant rates were similar across all cohorts analyzed (average 11.6%; p  = 0.546). Conclusions: In this nationwide analysis, our results suggest that over a recent five‐year period, conversion rates are highest when SCS trials are performed by neurosurgeons and orthopedic surgeons. The study has important implications for establishing uniform guidelines for training, patient selection, and education of physicians across multiple disciplines.